Comparative study on natural habitat of two closely-related conifer species (Pinus wallichiana A.B. jacks and pinus bhutanica grierson) - Tshering Choden (CNR, Lobesa Tshering Choden, 2022)
includes acknowledgement and abstract
Keywords: Thesis